A simulation of the number of particles trapped by the circulating filter of a hard disk drive and their trajectories - Thongsri, Jatuporn; Pongkom, Vana (My University, 2014)
A transition shear stress transport turbulence model and a discrete phase model of Fluent software were employed to simulate numerically the trajectories of loose particles and the number of them trapped by the circulating filter of a hard disk drive (HDD). The filter was located either at the left or the right of a 2.5 inch dual platter HDD rotating at 7200 rpm. Particles were released from the middle diameter position where four head gimbal assemblies (HGAs) were located. The simulation included airflow and particle trajectories released from any of the four HGAs. The results of this simulation can help determine the efficiency of a circulating filter and its optimal placement. © (2014) Trans Tech Publications, Switzerland.
Keywords: Airflow; Circulating filter; Hard disk drive; Particle trapped